Young offenders and the law : how the law responds to youth offending - Arthur, Raymond (New York, NY : Routledge, 2010)
How does the law deal with young offenders, and to what extend does the law protect and promote the rights of young people in conflict with the law? This title addresses these central issues and examines the legal response to the phenomenon of youth offending, and the contemporary forces that shape the law
1. Development of a separate youth justice system -- 2. Development of the youth justice system : 1900-69 -- 3. The youth justice system : from the Children and Young Persons Act 1969 to the present -- 4. The impact of international law on the development of the English youth justice system -- 5. The age of criminal responsibility and the defence of doli incapax -- 6. Protecting the welfare of young people who offend -- 7. Preventing youth offending -- 8. The role of the police and the youth court in tackling youth offending -- 9. Restorative justice in the English youth justice system -- 10. Sentencing options available to the youth court -- 11. Punishing parents for youth offending -- 12. Youth offending cases in the adult Crown Court
Includes bibliographical references and index
Keywords: Juvenile delinquency -- England; Juvenile justice, Administration of -- England